Vessel traits across a land use gradient in the tropical rainforests of Sabah, Malaysia - Palasiah Jotan (2019)
Ecological plant strategies are reflected in anatomical constraints and trade-offs, influencing the distribution of species in different environmental conditions. In trees, wood anatomical traits serve multiple ecological functions such as structural stability, nutrient storage and water conductance. Vessel traits may determine the response of trees to disturbance such as selective logging which affected vast areas of forests in Borneo and which has been shown to change abiotic conditions. Trade-offs in vessel traits reflect different strategies used by trees to deal with water transport under various environmental conditions. Vessel traits can be essential for the fitness of trees especially when exposed to extreme (hot and dry) conditions in open gaps of selectively logged forest. This study investigates the differences in community level of vessel traits expression between old-growth (OG) and selectively logged forest (SL) in Sabah, Malaysian Borneo and explores the ecological trait variation of trees in these two different forest types. A total of 356 mature trees were sampled, capturing 192 species. From cross sections of branches, vessel area (A) and vessel diameter (VD) were measured and vessel lumen fraction (F), vessel density (N), hydraulically weighted diameter (Oh), vessel area to number ratio (S) also called as a vessel composition metric, and potential hydraulic conductivity (Kp) were calculated. Across all species S varied 61-fold and N showed 15-fold variation. There were significant differences in A (x2=3.60; p=0.044), VD (x2=4.05; p=0.039) and Kp (x2=4.37; p=0.035) between OG and SL: vessel area and diameter were significantly larger in trees present in SL compared to OG forest. In SL, larger A and VD values also contributed to the hydraulic conductivity (Kp) being higher than that of OG forest. These differences in Kp can be explained by the presence of pioneer species in SL that represent fast growing trees which would need efficient water transport to support their fast growth rates. Therefore, logging in tropical forests drives differential expression of wood anatomical traits in response to the modified environments created by the disturbance. Vessel traits of common OG species adapted to ensure high hydraulic resistance when soil moisture is limiting while common species of SL developed an efficient water transport system but their vessels lacked hydraulic safety under stressful environmental conditions. The present study provided an important insight into vascular strategies of trees in Bornean rainforest and highlighted potential limitations on forest resilience during future climatic extremes.